Nursing Home Transfers for Behavioral Concerns: Findings from the OPTIMISTIC Demonstration Project. Issue 2 (20th November 2020) - Hathaway, Elizabeth E.; Carnahan, Jennifer L.; Unroe, Kathleen T.; Stump, Timothy E.; O'Kelly Phillips, Erin; Hickman, Susan E.; Fowler, Nicole R.; Sachs, Greg A.; Bateman, Daniel R.
Abstract : Objectives: To characterize pretransfer on‐site nursing home (NH) management, transfer disposition, and hospital discharge diagnoses of long‐stay residents transferred for behavioral concerns. Design: This was a secondary data analysis of the Optimizing Patient Transfers, Impacting Medical Quality, Improving Symptoms: Transforming Institutional Care project, in which clinical staff employed in the NH setting conducted medical, transitional, and palliative care quality improvement initiatives and gathered data related to resident transfers to the emergency department/hospital setting. R software and Microsoft Excel were used to characterize a subset of transfers prompted by behavioral concerns. Setting: NHs in central Indiana were utilized (N = 19). Participants: This study included long‐stay NH residents with behavioral concerns prompting transfer for acute emergency department/hospital evaluation (N = 355 transfers). Measurements: The measures used in this study were symptoms prompting transfer, resident demographics and baseline characteristics (Minimum Data Set 3.0 variables including scores for the Cognitive Function Scale, ADL Functional Status, behavioral symptoms directed toward others, and preexisting psychiatric diagnoses), on‐site management (e.g., medical evaluation in person or by phone, testing, and interventions), avoidability rating, transfer disposition (inpatient vs emergency department only), and hospital discharge diagnoses. Results: Over half of the transfers, 56%, had a medical evaluation before transfer, and diagnostic testing was conducted before 31% of transfers. After transfer, 80% were admitted. The most common hospital discharge diagnoses were dementia‐related behaviors (27%) and altered mental status (27%), followed by a number of medical diagnoses. Conclusion: Most transfers for behavioral concerns merited hospital admission, and medical discharge diagnoses were common. There remain significant opportunities to improve pretransfer management of NH transfers for behavioral concerns.